2021
DOI: 10.1101/2021.07.04.21259950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pneumococcal exposure routes for infants, a nested cross-sectional survey in Nha Trang, Vietnam

Abstract: Background: Infants are at highest risk of pneumococcal disease. Their added protection through herd effects is a key part in the considerations on optimal pneumococcal vaccination strategies. Yet, little is currently known about the main transmission pathways to this vulnerable age group. Methods and findings: We conducted a nested cross-sectional contact and nasopharyngeal swabbing survey in randomly selected infants across all 27 communes of Nha Trang, Vietnam. Bayesian logistic regression models were us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The observed asymmetry is consistent with <1-year-old infants being more susceptible to infections from within the household, and with the high proximity between mother and child. The exposure risk posed by adults has been observed in previous studies 33,34 , with routine vaccination of older children not found to have a significant effect on vaccine type carriage rates in unvaccinated infants 35 . Taken together, this suggests a possible benefit to a vaccination campaign targeting mothers or other adults with high contact rates to young infants before herd immunity in the adult population is established.…”
Section: Articlementioning
confidence: 72%
“…The observed asymmetry is consistent with <1-year-old infants being more susceptible to infections from within the household, and with the high proximity between mother and child. The exposure risk posed by adults has been observed in previous studies 33,34 , with routine vaccination of older children not found to have a significant effect on vaccine type carriage rates in unvaccinated infants 35 . Taken together, this suggests a possible benefit to a vaccination campaign targeting mothers or other adults with high contact rates to young infants before herd immunity in the adult population is established.…”
Section: Articlementioning
confidence: 72%
“…This asymmetry is consistent with <1 year old infants being more susceptible to infections from within the household, and with the high proximity between mother and child. The exposure risk posed by adults has been observed in previous studies (4345) with routine vaccination of older children found to not have a significant effect on vaccine type carriage rates in unvaccinated infants (46). Taken together this suggests there may be a benefit to a vaccination campaign targeting mothers or other adults with high contact rates to young infants before herd immunity in the adult population is established.…”
Section: Introductionmentioning
confidence: 75%
“…Most find a limited role of age and some short-lived protection from previous infection. However, other factors that can be context-specific, for example changing contact patterns as young children become more mobile and start attending daycare [43], may mask some of the age effects observed.…”
Section: Discussionmentioning
confidence: 99%